State-dependency and firm-level optimization: a contribution to Calvo price staggering - Peter McAdam; Alpo Willman (European Central Bank (ECB), 2007)
We implement a tractable state-dependent Calvo price-setting signal dependent on inflation and aggregate competitiveness. This allows us to derive a New Keynesian Phillips Curve (NKPC) expressed in terms of the actual levels of variables - rather than in-deviation from “steady state” form - and thus a specification which is not regime-dependent. A consequence of our approach is that ex-ante all firms face the same optimization problem. This state-dependent NKPC nests the conventional hybrid NKPC form as a special case. Finally, we demonstrate the uefulness of our approach by, first, analyzing the persistence and variability of inflation shocks under different inflation regimes and then comparing our state-dependent and timedependent NKPCs on US data.
Keywords: E31; E32; 330; Calvo Price Staggering; Firm-Level Optimization; New Keynesian Phillips Curves; Regime Dependency+; State-Dependency; Marktmechanismus; Preismanagement; New-Keynesian Phillips Curve; Inflationserwartung; Theorie; USA